Bank transparency, asset and liquidity risks - Yehning Chen; Iftekhar Hasan; Tuomas Takalo (Bank of Finland, 2025)
We study the effects of bank transparency on both banks' asset and liquidity risks, and ultimately, on banking sector stability and welfare. We show how enhanced bank transparency increases banks' vulnerability to excessive deposit outflows, but this threat of a liquidity crisis incentivizes banks to choose safer assets. We find that bank stability and welfare are a nonmonotonic function of transparency, and that they are maximized at an intermediate level of transparency, which is larger than the one preferred by banks but lower than what would result in excessive deposit outflows. Our model also suggests that bank transparency and deposit insurance are complementary policy tools, and that bank regulators should adjust disclosure requirements for banks procyclically
urn:nbn:fi-fe2025042229709
Keywords: G21; G28; D83; 330; bank transparency; bank runs; asset risk taking; banking stability; deposit insurance